Multiple factors predict longer and shorter time-to-ulcer-free in people with diabetes-related foot ulcers: Survival analyses of a large prospective cohort followed-up for 24-months. (March 2022) - Zhang, Yuqi; Cramb, Susanna; McPhail, Steven M.; Pacella, Rosana; van Netten, Jaap J.; Cheng, Qinglu; Derhy, Patrick H.; Kinnear, Ewan M.; Lazzarini, Peter A.
Highlights: Median time-to-(being)-ulcer-free in 4, 709 DFU patients was 112 days and 68.4% were ulcer-free within two years. Each year younger than 60 years was independently associated with longer time-to-ulcer-free. PAD and ulcer size were associated with longer time-to-ulcer-free but only for 6 months. Podiatry and knee-high offloading treatment were associated shorter time-to-ulcer-free. Probability of being ulcer-free was largest for geographical remoteness and PAD factors. Abstract: Aims: To investigate factors independently associated with time-to-(being)-ulcer-free, time-varying effects and predict adjusted ulcer-free probabilities, in a large prospective cohort with diabetes-related foot ulcers (DFU) followed-up for 24 months. Methods: Patients presenting with DFU(s) to 65 Diabetic Foot Services across Queensland, Australia, between July-2011 and December-2017 were included. Demographic, comorbidity, limb, ulcer, and treatment factors were captured at presentation. Patients were followed-up until ulcer-free (all DFU(s) healed), amputation, death or two years. Factors associated with time-to-ulcer-free were investigated using both Cox proportional hazards and flexible parametric survival models to explore time-varying effects and plot predicted adjusted ulcer-free probability graphs. Results: Of 4, 709 included patients (median age 63 years, 69.5% male), median time-to-ulcer-free was 112 days (IQR:40->730), with 68.4% ulcer-free within two years. Factors independently associated with longer time-to-ulcer-free were each year of age younger than 60 years, living in a regional or remote area, smoking, neuropathy, peripheral artery disease (PAD), ulcer size >1 cm 2, deep ulcer and mild infection (all p < 0.05). Time-varying effects were found for PAD and ulcer size limiting their association to six months only. Shorter time-to-ulcer-free was associated with recent DFU treatment by a podiatrist and receiving knee-high offloading treatment (both p < 0.05). Predicted adjusted ulcer-free probability graphs reported largest differences in time-to-ulcer-free over 24-months for geographical remoteness and PAD factors. Conclusions: Multiple factors predicted longer and shorter time-to-ulcer-free in people presenting with DFUs. Considering these factors, their time-varying effects and adjusted ulcer-free probability graphs, should aid the prediction of the likely time-to-(being)-ulcer-free for DFU patients.